Peningkatan Hasil Belajar Sifat-Sifat Bangun Ruang Dengan Menggunakan Model Cooperative Learning Tipe Jigsaw Kelas V Sekolah Dasar - Andani, Suci; Ahmad, Syafri; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to fine out the improvement of learning outcomes of the characteristics of geometry using Cooperative Learning model type Jigsaw at grade 5 SDN 06 Piai Tangah Padang. The type of research was classroom action research using qualitative and quantitative approaches. The subjects of this study were teachers and fifth grade students of SDN 06 Piai Tangah Padang. The increment of lesson plan assessment from the first cycle to the second cycle was 12.5%. In the activity of teachers, it increased from cycle I to cycle II by 16.05%. Furthermore, student activity increased by 11.1% from cycle I to cycle II. The average mathematics learning outcomes was 68.1 in cycle I it increased to 79.8 in cycle II. It would be concluded that the Cooperative Learning model type Jigsaw could improve the learning outcomes of the characteristics of geometry in grade 5 elementary school.